Particulate matter pollution in opencast coal mining areas: a threat to human health and environment. Issue 2 (17th February 2018) - Gautam, Sneha; Patra, Aditya Kumar; Sahu, Satya Prakash; Hitch, Michael
Abstract: With the increase in depth of mines, the movement and dispersion of particulate matter (PM) are very difficult to predict due to improper ventilation. Insufficient open pit ventilation remains the principal driver for the lack of dispersion and evacuation from mines and ultimately increases the time and amount of exposure to miners. Studies suggest that there is a direct and dependent relationship between the composition and exposure time to PM in mining operations. Furthermore, this paper helps the reader appreciate the need of carrying out studies to understand the nature of the dispersion of PM inside the mines.